Thermal performance of solar cooker with special cover glass of low-e antimony doped indium oxide (IAO) coating. (25th February 2017) - Ghosh, S.S.; Biswas, P.K.; Neogi, S.
Highlights: Evacuated glaze covered solar cooker has better thermal performance than uncoated. 32 different types of TCOs were experimented for high thermal insulation properties. Low-e IAO coated single glass covered solar cooker can be used. For domestic purpose, usage of low-e IAO glass is preferable specially in summer. Mainly due to low cost and ease of handling low-e IAO glass can be commercialized. Abstract: Indium, cadmium and tin based transparent conducting oxide (TCO) films have low thermal emissivity values and these are suitable for energy efficient applications where controlling of thermal effect is an important factor. Among these films antimony doped indium oxide (IAO) coated glass has been explored to have resistivity ∼2 × 10 −2 Ω cm. The film is homogeneous and good adherence to glass even in large dimensions [500 mm × 500 mm]. This film possesses emissivity ∼0.63 and it has been taken as the standard for the calculation of solar factor (gi ) and absorbed solar energy reradiated and convected indoors (Ei ) of transparent conducting oxide (TCO) films of 32 types. As calculated, the gi and Ei values of a TCO films are in the ranges 0.77–0.02 and 2.9–59 W m −2 respectively. Attempt has been made to use the IAO coated glass to improve glazing system in solar cooker with the principle that lowering of gi and Ei values would correspond to significant increase of heat insulation property. The thermal performance of solar cooker box having a cover of single layer low-e IAO coated glass was compared with the solar cooker box having a cover of uncoated double glaze soda lime silicate (SLS) glass initially and finally with the same solar cooker box with evacuated glazed cover maintaining vacuum (10 −3 atm) in the glazing system. Thermal performance of the solar cookers at ambient condition differs due to the variation of heat flow through glass cover with different glazing systems. The performance was promising for the solar cooker box with the cover of single glazed low-e IAO coated glass. The added advantages for domestic usage are low cost of production, relatively light weight and high mechanical durability along with relatively high thermal output.